Startup and defrosting dynamic characteristics of the heat pump and its influence on horizontal scroll compressor reliability of high-speed train - Che Wang; Qihang Wu; Jie Zhang; Zhaodong Zhang; Jianhua Wu (Case Studies in Thermal Engineering)
The heat pump is a crucial technology for reducing the energy consumption of air conditioning systems in high-speed trains. This paper experimentally investigates the startup and defrosting processes to evaluate potential reliability issues. Results indicate that, during startup, excessive refrigerant condensation in the cold compressor shell increases the oil sump level and lowers oil viscosity due to refrigerant dilution. These issues become more severe at lower ambient temperatures. During the defrosting process, a rapid decrease in discharge pressure causes the refrigerant to separate from the oil, significantly reducing the oil level. The low oil level period during defrosting is also extended at lower ambient temperatures, potentially leading to insufficient oil supply to the bearings. Since both oil viscosity and supply are crucial for the long-term reliable operation of the compressor, preheating and increasing the oil amount are suggested to improve the reliability of the heat pump.